Bi̇r akti̇f işgücü poli̇ti̇kası olarak işbaşı eği̇ti̇m programının çalışma hayatına etki̇leri̇ - Yazgan, Dilsun (My University, 2023)
Dünyada olduğu gibi Türkiye’nin de en temel problemlerden biri işsizliktir. Bu problemleri çözebilmek, en aza indirgemek adına aktif ve pasif olmak üzere Türkiye İş Kurumu tarafından düzenlenen politikalar bulunmaktadır. Çalışmanın amacı, Türkiye’de işsizlikle mücadele kapsamında Türkiye İş Kurumu tarafından belirlenen aktif İşgücü politikalarından biri olan İşbaşı Eğitim nın çalışma hayatına etkilerini incelemektir. Çalışmanın konusu, son dönemlerde hem işçi hem de işveren tarafından oldukça tercih edilen İşbaşı Eğitim nın neden bu denli tercih edildiği, Türkiye İş Kurumu tarafından işverenlere ne gibi ayrıcalıklar tanıdığı, bu program ile istihdam edilen işçilere ne gibi olanaklar sağladığı, işçilerin iş hayatında yer edinebilmeleri için neden bu programa başvurduğu detaylı bir şekilde incelenecektir. Tüm bunlarla birlikte, işbaşı eğitim programının işçi-işveren tarafından ekonomik boyutu da ele alınacaktır. Ayrıca işçi tarafından sosyolojik boyutu da incelenecektir. İşbaşı eğitim programının istihdama etkisi, işçi-işveren yönünden pozitif ve negatif etkileri detaylı bir şekilde ele alınacaktır. İşbaşı eğitim kavramı üzerine literatür taraması yapılarak çeşitli tez ve makaleler incelenmiştir. İşbaşı eğitim tezlerde, yapılan programın nasıl uygulandığı, programa katılım sağlanabilmesi için hangi şartların sağlanması gerektiği, programın olumlu ve olumsuz yönleri çeşitli şekillerde ele alınmıştır. Bu çalışmada, daha önce yapılan diğer çalışmalardan farklı olarak özellikle işçilerin uğradıkları hak kayıpları üzerinde durulacaktır. Bu konunun işsizlik sorunu ile mücadele yönteminin temel özelliklerini ortaya koymak açısından önemli olduğu düşünülmektedir. Çalışmada tez, makale diğer belgeler (rapor, dergi) incelenecektir. Literatür araştırmaları doğrultusunda aktif işgücü politikalarına gerek duyulma nedenleri, işbaşı eğitim programının son zamanlar hem işçi hem de işveren kanadında neden en çok tercih edilen aktif işgücü politikası olduğu ve bu politikanın sonuçları incelenecektir. ii Çalışma sonucunda işsizlik sorununa neden olan ekonomik ve sosyal faktörler hakkında bilgi verilecektir. Bu bilgilendirme doğrultusunda işsizlikle mücadele için önerilecek politikalar ve çalışmada esas değinilecek konu olan işbaşı eğitim erlendirilecektir.

Unemployment is one of the most fundamental problems in Turkey as well as in the world. In order to solve and minimize these problems, there are active and passive policies organized by the Turkish Employment Agency. The aim of the study is to examine the effects of on-the-job training program, which is one of the active labor policies determined by the Turkish Employment Agency within the scope of combating unemployment in Turkey, on working life. The subject of the study is why the on-the-job training program, which is highly preferred by both workers and employers recently, what privileges are given to employers by the Turkish Employment Agency, what opportunities it provides to the workers employed with this program, and why it has a place in the business life of workers. It will be examined in detail why they applied to this program in order to gain In addition to all these, the economic dimension of the on-the-job training program will be discussed by the employer-employee. In addition, the sociological dimension will be examined by the worker. The effect of the on-the-job training program on employment and its positive and negative effects in terms of workers and employers will be discussed in detail. Various theses and articles were examined by making a literature review on the concept of on the-job training program. In the theses about the on-the-job training program, how the program is implemented, what conditions must be met in order to participate in the program, the positive and negative aspects of the program are discussed in various ways. In some of these theses, it was carried out as a field study by conducting a survey with the people employed with the on-the-job training Program. The study, unlike previous field studies and other studies, will focus on the issue of whether the labor of workers, which has not been studied enough in the literature and has evolved into a more important problem as time goes by, whether the workers' labor is truly paid for and whether its employment can be continued. The reason for this detailed explanation is not to focus on a single point, but actually to focus on the method of combating the unemployment problem. iv In the study, thesis, article and other documents (report, journal) will be examined. In line with the literature research, the reasons for the need for active labor force policies, why the on-the-job training program has been the most preferred active labor policy for both workers and employers in recent times, and the results of this policy will be examined. In this study, unlike other previous studies, the focus will be on the loss of rights suffered by workers. It is thought that this issue is important in terms of revealing the basic features of the method of combating the unemployment problem. As a result of the study, information will be given about the economic and social factors that cause the unemployment problem. In line with this information, the policies to be proposed to combat unemployment and the on-the-job training program, which will be the main subject of the study, will be evaluated.
The effects of the on-the-job training program as an active labor policy on working life
Keywords: Active Labor Policies; Aktif İşgücü Politikaları; Employment; İstihdam; İş hayatında kalite; İşbaşı Eğitim Programı; İşsizlik; On-the-Job Training Program; Quality of wor life; Social Security Institution; Sosyal Güvenlik Kurumu; Turkish Employment Agency; Türkiye İş Kurumu; Unemployment